Analisis Tikungan Spiral-Spiral pada Tikungan Tapal Kuda Cianjur dengan Metode Jarak Pandang Henti - Prayudyanto, Muhammad Nanang; Yasid, Viki Handika; Alimuddin, Alimuddin; Taqwa, Fadhila Muhammad Libasut; Sudrajat, Endang (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
A large number of bends in Cianjur Regency makes the Cianjur Regency area prone to traffic accidents, especially for heavily loaded vehicles, one of the corners that often occurs in cases of accidents on heavily loaded vehicles is the Tapal Kuda Cianjur bend. The problem with bend Tapal Kuda Cianjur is that the bend has a small radius so it makes the curve very sharp in uphill road conditions so it is very difficult for heavily loaded vehicles to pass corners and resulting in accidents on heavily loaded vehicles. The method used is a geometric analysis method to provide an overview of field conditions and stop visibility distance analysis which aims to determine the stopping visibility on the corner so that it is expected to meet the standards set by Bina Marga so that the view of the road users when passing a corner is not blocked. The results of the geometric analysis show that the bend is still feasible to accommodate traffic loads, the bend has a spiral-spiral shape with a value of Rc=30 m, Ts= 40,599 m, Es=9,152 m with a stop visibility value at the existing condition =17,300 m and does not comply with the provisions in the minimum stop visibility distance table. So it is necessary to improve the shape of the bend using a planned speed of 60 km / h, improvement of the shape of the bend is planned using the form of SCS and FC with values of Rc= 120 m and Rc=500 m and total arc SCS=196,878 m, FC=611,982 m with the value of the repair bend stop visibility distance repair bend both spiral-circle-spiral and full circle shapes of 82,117 m and in accordance with the provisions set by Bina Marga.